2023
DOI: 10.3390/ijms24108950
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in Human Fertility and Infertility

Abstract: In human spermatozoa and oocytes (and their surrounding granulosa cells), mitochondria carry out important functions relating to human fertility and infertility. Sperm mitochondria are not transmitted to the future embryo, but are closely related to the generation of energy needed for sperm movement, capacitation, and acrosome reactions, as well as for sperm–oocyte fusion. On the other hand, oocyte mitochondria produce energy required for oocyte meiotic division and their abnormalities can thus cause oocyte an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was reported that necrosis fosters mitochondrial dysfunction due to inner membrane depolarization, mitochondrial swelling, and rupture, resulting in the loss of ATP production [36]. Mitochondrial damage that occurs in oocytes during their long life span is recognized as one of the most important factors that adversely affect fertility in humans [37]. Furthermore, a significant increase in the diameter of overactivated eggs (Figures 1, 2, 4 and 7) indicates that membrane permeability is augmented and cellular osmotic homeostasis is lost in these eggs.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that necrosis fosters mitochondrial dysfunction due to inner membrane depolarization, mitochondrial swelling, and rupture, resulting in the loss of ATP production [36]. Mitochondrial damage that occurs in oocytes during their long life span is recognized as one of the most important factors that adversely affect fertility in humans [37]. Furthermore, a significant increase in the diameter of overactivated eggs (Figures 1, 2, 4 and 7) indicates that membrane permeability is augmented and cellular osmotic homeostasis is lost in these eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial impairment has been pointed out as an aging hallmark [ 3 , 17 , 21 , 31 , 36 ], and its involvement in oocyte deterioration in AMA women has already been described [ 37 , 38 ]. Abnormalities in mitochondrial ultrastructure, dynamics and integrity, metabolism, and mtDNA mutations and deletions [ 17 ] have been studied in follicular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria play a pivotal role in cellular energy production through oxidative phosphorylation, serving as vital regulators of energy metabolism, metabolic homeostasis, and oxidative stress management, thus exerting significant influence over reproductive aging processes. Within germ cells, mitochondria fulfill indispensable roles in supporting energy-intensive processes such as oocyte maturation, fertilization, and subsequent embryonic development [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%